Experimental study on solidification of sludge by mixing reclaimed activated micro powder of waste concrete with industrial solid waste - Wang, Shuai; Wang, Aixun; Fu, Xudong; Hong, Xinliang; Zhang, Yiru; Zhang, Xianwei; Li, Zhe; Wang, Yaning; Li, Shenghao; Shen, Yuquan (Frontiers in Built Environment, 2025)
The effective disposal of construction and industrial solid waste is vital for sustainable urban development. This study developed a composite cementitious material (CCM) based on mechanically activated waste concrete, blast furnace slag, and carbide slag for sludge solidification. Through paste tests, unconfined compressive strength (UCS), and durability tests, the optimal CCM mix was determined as 30% waste concrete, 60% blast furnace slag, 10% carbide slag, and 10% anhydrous sodium sulfate. After 7 and 28 days of curing, the CCM paste blocks achieved UCS values of 10.89 MPa and 14.17 MPa, respectively. With 18% CCM content, the solidified sludge attained a UCS of 0.82 MPa after 14 days, meeting the bearing strength requirement (≥0.8 MPa) for China’s first-class highways. It also exhibited excellent durability, with a water stability coefficient of 88.5% and even slightly increased UCS after freeze-thaw cycles. X-ray diffraction (XRD) and Scanning Electron Microscopy-Energy Dispersive Spectrometer (SEM-EDS) analyses revealed that hydration products such as ettringite (AFt), dicalcium silicate (C2S), and calcium aluminosilicate hydrate (C-A-S-H) intertwined and cemented sludge particles, enhancing structural density and contributing to improved mechanical and durability performance.